Use of hypoxia dosed to slow age-related changes organism seniors - Nazariy Fedynyak (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to carry out a detailed analysis of current scientific views on the use of dosage hypoxia to enhance functionality and slowing premature aging of the human body older and older. Material and Methods: the research work leading domestic and foreign scholars who have studied this problem. Results: found that the use of hypoxic effects on the human body and elderly seniors is a safe and effective way to increase the functional state anti-hypoxic mechanisms which are a key component in the determination of the aging process. Conclusion: found that short-term hypoxic effects that are useful for older age groups is no less effective than a long term.